Comparative outcomes of lopinavir/ritonavir and hydroxychloroquine for the treatment of COVID-19 with mild-to-moderate severity: A retrospective observational study. Issue 1 (January 2021) - Lee, Jeong Eun; Lee, Soon Ok; Heo, Jeonghun; Kim, Dong Wan; Park, Mi Ran; Son, Hyunjin; Kim, Dongkeun; Kim, Kye-Hyung; Lee, Shinwon; Lee, Sun Hee
Background: Lopinavir/ritonavir (LPV/r) and hydroxychloroquine (HCQ) are both being used to treat coronavirus disease 2019 (COVID-19), but their relative effectiveness is unknown. The purpose of this study was to compare the clinical outcomes of patients treated for COVID-19 with LPV/r or HCQ. Methods: A retrospective observational study was conducted at 2 hospitals in Busan, South Korea, where approximately 90% of COVID-19 patients were hospitalised during February/March 2020. All patients aged ≥15 years that were hospitalised with mild or moderately severe COVID-19 received LPV/r or HCQ as their initial treatment and were included in the analysis. Results: Among the 72 patients with mild-to-moderate disease severity on admission, 45 received LPV/r and 27 received HCQ as their initial therapy. A higher proportion of the LPV/r group had pneumonia on admission (LPV/r, 49% vs HCQ, 15%), but there were no other significant differences in the demographic or clinical characteristics between groups. Switching therapy due to clinical failure was significantly more common in the HCQ group than in the LPV/r group (41% [11/27] and 2% [1/45], respectively, P = .001). Disease progression was also significantly more common in the HCQ group than in the LPV/r group (44% [12/27] and 18% [8/45], respectively, P = .030). Conclusion: Based on our study results, HCQ shows no apparent advantage compared to LPV/r for preventing progression to severe disease in patients with COVID-19.